A Randomized, Evaluator-Blind, Split-Face Study Evaluating the Safety and Efficacy of Calcium Hydroxylapatite for Jawline Augmentation. Issue 1 (January 2022) - Boen, Monica; Alhaddad, Marwan; Goldman, Mitchel P.; Kollipara, Ramya; Hoss, Elika; Wu, Douglas C.
Abstract : INTRODUCTION: Jawline augmentation with calcium hydroxylapatite has not yet been evaluated in a prospective study with a split-face design. This study aims to perform the first randomized controlled, split-face study on the efficacy and safety of calcium hydroxylapatite for jawline augmentation using the needle and cannula technique. OBJECTIVE: To perform the first randomized controlled, split-face study on the efficacy and safety of calcium hydroxylapatite for jawline augmentation using the needle and cannula technique. MATERIALS AND METHODS: This is a single-site, randomized, evaluator-blind trial enrolling a total of 10 healthy subjects with at least Grade 1 (mild) on a 4-point Jawline Scale. One side of the face was randomized to receive 1 to 2 syringes of calcium hydroxylapatite with lidocaine (total of 3 mL) for correction of wrinkles and folds along the jawline using both the cannula and needle method, and a balancing treatment will be performed 1 month later. Blinded investigator and subject evaluations will be performed immediately after treatment and at the 30-, 60-, and 90-day visits. RESULTS: Ten subjects were enrolled and completed the trial. There was a improvement in the degree of wrinkling and skin sagging in the 4-point Jawline Scale, with an average of a 1.3-point improvement in the scale on the day of treatment and at the Day 30 visit, which remained improved greater than baseline after 3 months as graded by blinded investigators. The Clinician Global Aesthetic Improvement Score for the treated side versus control, as assessed by blinded investigators, demonstrated a improvement with a 2.3-point improvement on the 5-point scale, and by the final visit on Day 90, most patients had a much improved appearance from baseline. CONCLUSION: This study demonstrates that calcium hydroxylapatite is effective and safe for restoration and augmentation of the jawline using the unique needle and cannula technique. Abstract : Supplemental Digital Content is Available in the Text.